Bacterial and Fungal Contaminants in Mycobacterium tuberculosis Cultures at National Tuberculosis Referral Laboratory-Kampala - Vianney, Tushabe John; Esther, Katuura; Stanley, Iramiot J. (Microbiology Research Journal International, 2017)
Aim: This study was aimed at identification of fungal and bacterial contaminants in Tuberculosis cultures at the Uganda National Reference Laboratory (NTRL). Methods: The cultures were previously grown on Lowenstein-Jensen (LJ) medium in bottle slants. The method used involved conventional culture methods and biochemical characterization of the contaminants. Bacterial cultures were carried out in both aerobic and carbon dioxide incubators where required and to the respective temperatures of the organisms. Growth was observed between 24-48 hours for bacterial and up to 72 hours for yeast contaminants. Cultures on SDA were also monitored for three weeks for possible growth of filamentous fungi. Results: The identified bacteria mostly included; S. pyogenes, S. aureus, E. coli, P. aeruginosa, K. pneumoniae, and least isolated were; S. marcescens, H. influenza, S. pneumoniae and B. subtilis Fungal contaminants were A. fumigatus and C. albicans. Conclusion: Based on this study a relatively increased level of contamination was noted. We recommend that high level of aseptic techniques be maintained in addition to the current standards in order to reduce the level of bacterial and fungal contaminants in TB cultures so as to improve the detection rate of Mycobacteria tuberculosis by culture method.
Keywords: Bacteria; Contaminants; Mycobacterium tuberculosis